Participation-based clinical clerkships contribute to increased medical student confidence in community emergency care: a cohort study - Hiroshi Mihara; Atsushi Jinno; Kenta Sato; Kazuhito Nomura; Takao Wakabayashi; Yoshihisa Tsuji (BMC Medical Education)
Abstract Background The Community-based assessment for Clinical and Emergency Practice (C-CEP) scale is a validated tool comprising 15 items across four components: “Attitude and Communication in Emergency Medicine,” “Basic Clinical Skills,” “Knowledge about Community Medicine,” and “Knowledge in Evidence-Based Medicine.” The C-CEP scale enables medical students’ self-assessment of their confidence in clinical and emergency care. This study aimed to evaluate whether a two-week comprehensive general practice clerkship would improve C-CEP scores and to identify the specific training elements contributing to increased confidence in primary care, particularly in emergency responses. Methods After obtaining ethical approval and written informed consent, fifth-year medical students at Sapporo Medical University who participated in two-week off-campus clerkships at external healthcare facilities (hospitals) during the 2023 academic year were included. Pre- and post-clerkship C-CEP scores were collected. Changes in the baseline and average scores were analyzed across facilities accepting more than four trainees. Text mining was conducted on students’ reflective portfolios from the facilities with significant findings to identify frequent and co-occurring words related to confidence-building activities. Results Out of 115 eligible participants, 97 students were included in the analysis (84.3% participation rate). The data from seven facilities accepting more than four trainees, representing 74 students in total, were analyzed. These facilities averaged 243 beds, were located 147 km from the medical school, and had an emergency admission rate of 84.6%. C-CEP scores showed significant improvement across all components post-clerkship (p < 0.05). Although pre-clerkship scores did not differ significantly across facilities, post-clerkship score increases varied. Multivariate analysis identified Facilities D and F as exhibiting significant differences in confidence improvement compared with the other facilities (R² = 0.20, p = 0.0379). Text mining highlighted that Facility F emphasized active learning activities such as “interviews,” “examinations,” and “conferences,” whereas Facility D focused on passive activities such as “observation”, which were associated with limited impact on trainee confidence. Conclusion The C-CEP effectively measured confidence improvements in primary care and emergency responses among fifth-year medical students following their clinical clerkships. The C-CEP scale’s ability to detect inter-facility differences highlights its potential to inform and refine clinical education programs, ensuring more targeted and effective training.